Identification of new binding partners of the chemosensory signaling protein Gγ13 expressed in taste and olfactory sensory cells - Liu, Zhenhui; Fenech, Claire J.; Cadiou, Hervé; Grall, Sylvie; Tili, Esmerina; Laugerette, Fabienne; Wiencis, Anna; Grosmaitre, Xavier; Montmayeur, Jean-Pierre (Frontiers in Cellular Neuroscience, 2012)
Tastant detection in the oral cavity involves selective receptors localized at the apical extremity of a subset of specialized taste bud cells called taste receptor cells (TRCs). The identification of the genes coding for the taste receptors involved in this process have greatly improved our understanding of the molecular mechanisms underlying detection. However, how these receptors signal in TRCs, and whether the components of the signaling cascades interact with each other or are organized in complexes is mostly unexplored. Here we report on the identification of three new binding partners for the mouse G protein gamma 13 subunit (Gγ13), a component of the bitter taste receptors signaling cascade. For two of these Gγ13 associated proteins, namely GOPC and MPDZ, we describe the expression in taste bud cells for the first time. Furthermore, we demonstrate by means of a yeast two-hybrid interaction assay that the C terminal PDZ binding motif of Gγ13 interacts with selected PDZ domains in these proteins. In the case of the PDZ domain-containing protein zona occludens-1 (ZO-1), a major component of the tight junction defining the boundary between the apical and baso-lateral region of TRCs, we identified the first PDZ domain as the site of strong interaction with Gγ13. This association was further confirmed by co-immunoprecipitation experiments in HEK 293 cells. In addition, we present immunohistological data supporting partial co-localization of GOPC, MPDZ, or ZO-1, and Gγ13 in taste buds cells. Finally, we extend this observation to olfactory sensory neurons (OSNs), another type of chemosensory cells known to express both ZO-1 and Gγ13. Taken together our results implicate these new interaction partners in the sub-cellular distribution of Gγ13 in olfactory and gustatory primary sensory cells.